Análisis de rendimiento y productividad de formaleta cilíndrica prefabricada, utilizada en la construcción de columnas del Country Day School - Zamora-Pereira, Fabiola (Instituto Tecnológico de Costa Rica, 2016)
This project consists in to determine the productivity and performance of the workforce in the process of shuttering columns with circular section, of the Country Day Project School, located in Hacienda Espinal, Alajuela. The Work Sampling technique, which consist constantly observing the activity studied, was used to determine productivity in the process of formwork, determining what percentage of time is productive (PT), contributory (CT) or noncontributory (NCT), and according to the results the workers for this activity take in about 44% TP, 13% of TC and 43% TNC. The Crew Balance methodology was used for the stripping process, which determined an efficiency of 66% for this activity. Besides this, the yields of the 4 necessary sub-activities for making the columns were determined, which are fitting armor 0.023Hr-H / kg, setting the formwork and the accessories 1.49Hr-H / m2, for the pouring of the column was determined that the yield was 4.42Hr-H / m3 and the stripping performance was established by 0.3Hr- H / m2. Since this study is focused in the workforce, brief interviews were made, in which the workers were questioned about the factors that as per their experience reduce the productivity and performance in their daily work.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Colado; Encofrado; Work sampling; Crew Balance; Mano de obra